Smart car-security system using Global System for Mobile and Global Positioning System: article / Mohd Fadzli Mohd Salleh - Mohd Salleh, Mohd Fadzli (2013)
In Malaysia, car stolen cases are considered high even that recent statistic has shown that the percentage has decreased. The percentage of stolen car is decreasing because of the number of cars being registered on the road is high every year. To prevent the cars from being stolen, car manufacturer has equipped each car that they produced with a simple one-way communication alarm system. This factory-equipped system is not enough to prevent the car from being stolen. The objective of this research is to provide a system that can prevent the car from being stolen or relocating the car after it has been hijacked. The proposed system is designed by taking advantage of the Global Positioning System (GPS), and Global System for Mobile Communication (GSM) technology.